PENGARUH MOTIVASI, DISIPLIN DAN LOYALITAS KERJA TERHADAP KINERJA GURU SMA UNGGULAN AL-AZHAR MEDAN - Pulungan, Halomoan; Sinto; Sukarsih, Sukarsih (Fakultas Ekonomi Universitas Al-Azhar Medan, 2024)
this study was to determine the effect of motivation, discipline and work loyalty on the performance of teachers at Al-Azhar Senior High School Medan. The sample of this research is the teacher at the Al-Azhar Senior High School Medan with 51 samples of respondents. The statistical method used is multiple linear regression (multilinear regression analysis). The results of this study prove that partially motivation (X1) has a positive and significant effect on Teacher Performance (Y), with a t-count value of 7.149 and a significance level value of 0.001, partially Discipline (X2) has a positive and significant effect on Teacher Performance (Y) , with a t-count value of 9.191 and a significance level value of 0.003, partially work loyalty (X3) has a positive and significant effect on Teacher Performance (Y), with a t-count value of 12.307 and a significance level value of 0.000, Simultaneously Motivation (X1) , Discipline (X2) and work loyalty (X3) have a positive and significant effect on Teacher Performance, with a calculated F value of 57.182 and a significance level of 0.000. With a coefficient of determination (R2) of 0.883 (88.3%).